Factors affecting the gross domestic product in Iraq for the period 1990-2018 - Noori Alhamdany, Saad (International Journal of Psychosocial Rehabilitation, 2020)
"The study aimed to measure and analyze the effect of some factors such as (government spending GO, consumption CO, population PO, investment IO, exchange rate EX, money supply Ms, and inflation Inf) in the gross domestic product, however, the research adopted the descriptive and standard approach in the formation of the model based on Economic theory and statistical program (Eviews) during the period (1990-2018), and the importance of the study comes from that the gross domestic product is a basic indicator for identifying the performance of the economy, the research also relied on the tests of Augmented Dickey-Fuller and PhilipsByron to recognize the stationarity of the variables, and the results showed the significance of the variables through the value of the calculated F factor of 85.334 at the level of significance of 5% As for the 1.76 test (D.W), it proves that there is no autocorrelation problem, and the value of the adjusted determination coefficient R2 showed that about 95% of the changes in the GDP were explained by the independent variables. while the 5% remaining of these changes can be attributed to other factors that are not included in the model. However, government and investment expenditures were excluded from the model because they were not significant, and the study recommended setting targeted policies to improve and develop the investment climate".